Expressive and receptive use of speech and graphic symbols by typically developing children: What skills contribute to performance on structured sentence-level tasks? - Sutton, Ann; Trudeau, Natacha; Morford, Jill P.; Smith, Martine M. (International Journal of Speech-Language Pathology, 2021)
To explore expressive and receptive use of speech and graphic symbols and relationships with linguistic and cognitive skills in children with typical development. Participants were 82 children with typical development (4 to 9 years). Measures of memory, visual analysis skills, and receptive language were used, along with five experimental tasks with speech or symbols as input (stimulus) or output (response), using single clause and compound clause stimuli. Cluster analysis grouped participants with similar performances patterns, who were then compared on linguistic and cognitive skill measures. The lowest performing group sometimes accurately interpreted graphic symbol utterances that were visible during responding. The mid-performing group was stronger on expressive than receptive symbol utterances when the model did not remain visible. The highest group was comparable on expressive and receptive symbol tasks, but nonetheless stronger with spoken utterances. Relationships of linguistic and cognitive skills with task performance differed across the clusters. The findings help clarify the input-output modality asymmetry in graphic symbol communication. Spoken language proficiency does not directly transfer to sentence-level expressive and receptive graphic symbol use. Exploring potentially challenging sentence-level phenomena is important. Research is warranted to explore developmental progressions and potential clinical applications more systematically.